The development of a clinical research educational training for community health workers using the joint task force for clinical trial competency framework - Yakubov, Amin; Pimenova, Dina; Ahmed, Alzahraa; Corvacho, Romelia; Madigan, Joanna; Naik, Jay; Lyu, Chen; McFarlane, Anita; Foster, Victoria; Haseltine, Megan; Trifonov, Alexandr; Cabrera, Ivette; et al. (Frontiers in Pharmacology, 2023)
Community Health Worker (CHW) is an umbrella term for an array of health practitioners who operate under various titles globally and whose overarching mission is to serve and engage the needs of culturally distinct communities toward improving health outcomes. Titles include community health workerCHW, patient navigator, promotora, outreach specialist, community advocate, and community health educator, among others (1). CHWs are essential frontline public health professionals who leverage their intimate understanding of local communities and often serve as trusted intermediaries between the members of those communities and both medical and social service systems. Equipped with an understanding of their community's cultural characteristics, behaviors, and attitudes, CHWs are uniquely positioned to explain and navigate individuals through complex health systems and to communicate individual, family, and community-level needs to service providers to improve access to, and quality of, care. Through this integral "bridging" work, CHWs enhance the self-sufficiency and knowledge of community members and the community itself, strengthen relationships with service delivery agencies, and influence attitudes and practices through education, informal counseling, social support, and advocacy (1, 2, 32,3,4).